Remarks by World Bank Group President David Malpass to the Development Committee – 2022 Spring Meetings - Malpass, David (World Bank, Washington, DC, 2022)
These remarks were delivered by World Bank Group President David Malpass to the Development Committee at 2022 Spring Meetings on April 22, 2022. In the case of Ukraine, the World Bank Group is doing everything we can to assist during the crisis. We have already mobilized more than 3 billion dollars of support, enlarged by your grants, guarantees, and parallel financing. We are also exploring other innovative financing options to support countries hosting Ukrainian refugees. Together with the IMF and other IFIs we are sending a clear signal that we stand with the Ukrainian people during these difficult times. The World Bank Group has made significant progress over the past decade in our engagements with countries facing challenges across the full spectrum of fragility, conflict, and violence. The Bank expects to have committed 11 billion dollars to purchase and deploy vaccines by the end of our fiscal year, benefiting 81 countries. As the world faces crises of refugees and IDPs, digitalization is creating new jobs, expanding financial inclusion, and improving the delivery of health, education, and social protection programs. It is also increasing the quality of government services, enhancing accountability, and reducing opportunities for corruption. The World Bank Group can work with the public and private sectors, in collaboration with other development partners, to develop and expand access to solutions aimed at harnessing the full potential of digital transformation.